Droplet-on-demand mass spectrometry reveals curvature-dependent interfacial reactivity in aqueous microdroplets - Yu Xia; Xufeng Gao; Juan Li; Richard N. Zare; Bolei Chen; Xinxing Zhang (Proceedings of the National Academy of Sciences, 2025)
Water microdroplets offer a chemical environment that can dramatically accelerate reaction rates compared to bulk-phase solutions and even drive chemical transformations not found in bulk solutions. While mass spectrometry has proven indispensable for studying microdroplet chemistry, current methods rely on ensemble-averaged data from polydisperse droplet populations, obscuring the molecular details and droplet-size dependencies of reactions in individual droplets. Here, we present a piezoelectric-driven droplet-on-demand platform that enables direct mass spectrometric analysis of single, size-controlled microdroplets. We demonstrate a broad range of reactions occurring within isolated droplets. These reactions yield products comparable to those generated in conventional spray-based microdroplet systems, confirming that enhanced reactivity is intrinsic to the microdroplet environment. Crucially, we reveal a pronounced droplet-size-dependent reactivity, with smaller droplets exhibiting markedly higher activity per unit surface area. This consistent trend across different reaction types underscores the pivotal role of curvature-modulated interfacial electric fields in governing microdroplet reaction dynamics. Higher electric field strengths cause more radicals to be formed, but these radicals recombine with one another, removing them for reactions with other substrates. Consequently, as our experimental data show, there is an optimum droplet size to yield the highest product reaction rate.